Pelatihan Pengolahan Microsoft Excel untuk Membuat Bank Soal Bagi Guru SD Gugus V Lingsar - Amrullah Amrullah; Nani Kurniati; Muhammad Turmuzi; Ni Made Intan Kertiyani; Wahidaturrahmi Wahidaturrahmi (Rengganis Jurnal Pengabdian Masyarakat, 2022)
Utilization of technology, information and communication, especially the use of software such as Microsoft Word, Microsoft Power Point and Microsoft Excel is an ability that must be possessed by elementary school teachers in implementing an independent curriculum. The use of Microsoft Excel, for example, can assist teachers in processing various data, such as processing assessment instruments in the form of end-of-semester assessment questions for students. Based on interviews with the group leader V Lingsar, the results showed that teachers still needed time in making final semester assessment questions, starting from making question banks, sorting and randomizing questions into several question packages. To answer these problems, a service activity was carried out in the form of training on the use of Microsoft Excel to create a question bank. The training was attended by 20 teachers of the V Lingsar group. This activity consists of two sessions, namely the delivery of material and guided practice. All participants felt that the material could be understood well, guided practice could be carried out smoothly and this activity could be relevant to the needs of the teacher.